Visceral fat is associated to the severity of COVID-19 - Favre, Guillaume; Legueult, Kevin; Pradier, Christian; Raffaelli, Charles; Ichai, Carole; Iannelli, Antonio; Redheuil, Alban; Lucidarme, Olivier; Esnault, Vincent (Metabolism, clinical and experimental, 2021)
Excess visceral fat (VF) or high body mass index (BMI) is risk factors for severe COVID-19. The receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is expressed at higher levels in the VF than in the subcutaneous fat (SCF) of obese patients. To show that visceral fat accumulation better predicts severity of COVID-19 outcome compared to either SCF amounts or BMI. We selected patients with symptomatic COVID-19 and a computed tomography (CT) scan. Severe COVID-19 was defined as requirement for mechanical ventilation or death. Fat depots were quantified on abdominal CT scan slices and the measurements were correlated with the clinical outcomes. ACE 2 mRNA levels were quantified in fat depots of a separate group of non-COVID-19 subjects using RT-qPCR. Among 165 patients with a mean BMI of 26.1 ± 5.4 kg/m2, VF was associated with severe COVID-19 (p = 0.022) and SCF was not (p = 0.640). Subcutaneous fat was not different in patients with mild or severe COVID-19 and the SCF/VF ratio was lower in patients with severe COVID-19 (p = 0.010). The best predictive value for severe COVID-19 was found for a VF area ≥128.5 cm2 (ROC curve), which was independently associated with COVID-19 severity (p < 0.001). In an exploratory analysis, ACE 2 mRNA positively correlated with BMI in VF but not in SCF of non-COVID-19 patients (r2 = 0.27 vs 0.0008). Severe forms of COVID-19 are associated with high visceral adiposity in European adults. On the basis of an exploratory analysis ACE 2 in the visceral fat may be a trigger for the cytokine storm, and this needs to be clarified by future studies. •Visceral fat is associated with COVID-19 severity in Caucasian adults.•The expression of angiotensin converting enzyme type 2, the receptor of SARS-Cov2, in visceral fat may contribute to the cytokine storm.•Metabolic health of patients with COVID-19 should be carefully evaluated.